Computerized Symbol Digit Modalities Test in a Swiss Pediatric Cohort – Part 2: Clinical Implementation - Klein, Marie-Noëlle; Jufer-Riedi, Ursina; Rieder, Sarah; Hochstrasser, Céline; Steiner, Michelle; Cao, Li Mei; Feinstein, Anthony; Bigi, Sandra; Lidzba, Karen (Frontiers in Psychology, 2021)
Background: Information processing speed (IPS) is a marker for cognitive function. It is associated with neural maturation and increases during development. Traditionally, IPS is measured using paper and pencil tasks requiring fine motor skills. Such skills are often impaired in patients with neurological conditions. Therefore, an alternative that does not need motor dexterity is desirable. One option is the computerized Symbol Digit Modalities Test (c-SDMT), which requires the patient to verbally associate numbers with symbols. Method: Eighty-six participants (8–16 years old; 45 male; 48 inpatients) were examined, 38 healthy and 48 hospitalized for a non-neurological disease. All participants performed the written SDMT, c-SDMT and the Test of Nonverbal Intelligence Fourth Edition (TONI-4). Statistical analyses included a multivariate analysis of covariance (MANCOVA) for the effects of intelligence (IQ) and hospitalization on the performance of the SDMT and c-SDMT. A repeated measures analysis of variance (repeated measures ANOVA) was used to compare performance across c-SDMT trials between inpatients and outpatients. Results: The MANCOVA showed that hospitalization had a significant effect on IPS when measured with the SDMT (p = 0.04) but not with the c-SDMT (p = 0.68), while IQ (p = 0.92) had no effect on IPS. Age (p < 0.001) was the best predictor of performance of both tests. The repeated measures ANOVA revealed no significant difference in within-test performance (p = 0.06) between outpatient and inpatient participants in the c-SDMT. Conclusions: Performance of the c-SDMT is not confounded by hospitalization and gives within-test information. As a valid and reliable measure of IPS for children and adolescents, it is suitable for use in both inpatient and outpatient populations.